Enhancing Nursing Knowledge and Practice in a Rehabilitation Assisted Living Facility Through an Evidence-Based Pressure Injury Prevention Education Model - Nicole M. West; Tiffany J. Calderon; Carrie L. Buch (Journal of Gerontological Nursing, 2026)
Purpose: Pressure injuries are a persistent problem in assisted living facilities (ALFs), especially among patients aged ≥65 years who have limited mobility. Enhancing nursing knowledge and adherence to evidence-based prevention strategies is essential. The current quality improvement project implemented the Agency for Healthcare Research and Quality (AHRQ) Pressure Injury Prevention Toolkit to strengthen nursing practices in an ALF rehabilitation unit. Method: Over 6 weeks, 11 nurses participated in modular workshops on the Braden Scale, skin assessments, repositioning, nutrition, support surfaces, staging, and individualized care planning. Nursing knowledge was measured using the Pressure Ulcer Knowledge Test (PUKT) before and after the intervention. Thirty-five care plans were audited postintervention for prevention strategy documentation. Results: PUKT scores increased from 80.7% to 97.4%. Of the 35 care plans, 94% documented prevention strategies, including 100% repositioning and Braden Scale use, 97% skin assessments, 91% incontinence care, and 85% nutritional support. Conclusion: Targeted education improved nursing knowledge and documentation, supporting evidence-based care for older adults.